2019
DOI: 10.1038/s41598-019-49064-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Photodynamic Therapy with Redaporfin on Tumor Oxygenation and Blood Flow in a Lung Cancer Mouse Model

Abstract: Three photodynamic therapy (PDT) protocols with 15 min, 3 h and 72 h drug-to-light time intervals (DLIs) were performed using a bacteriochlorin named redaporfin, as a photosensitizer. Blood flow and pO 2 changes after applying these protocols were investigated in a Lewis lung carcinoma (LLC) mouse model and correlated with long-term tumor responses. In addition, cellular uptake, cytotoxicity and photocytotoxicity of redaporfin in LLC cells were evaluated. Our in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 60 publications
(74 reference statements)
0
30
0
1
Order By: Relevance
“…Furthermore, Madsen et al demonstrated the ability of Trojan horse cell delivery using immune cells to cross PDT‐opened BBB (Madsen et al., 2013), which remarks that not only high weight molecules can reach brain parenchyma after PDT but also, the opening of tight junctions with formed pores are big enough to lead the passage of cells. Considering that one of the most studied effects of PDT consists of the vascular damage which is achieved by controlling the time interval between PS intravascular injection and illumination, the photoinduced damage of ECs could cause massive destruction that produce vessel collapse and thrombus formation (Karwicka et al., 2019; Lepor, 2008). However, in targeted vascular PDT and with the aim of generating leakage from capillaries, appropriate irradiation dosage must be managed to increase vessel permeability but not induce occlusion; because in this last scenario the arrival of drugs and cells to tumor may be interrupted.…”
Section: The Opening Of Bbb By Pdtmentioning
confidence: 99%
“…Furthermore, Madsen et al demonstrated the ability of Trojan horse cell delivery using immune cells to cross PDT‐opened BBB (Madsen et al., 2013), which remarks that not only high weight molecules can reach brain parenchyma after PDT but also, the opening of tight junctions with formed pores are big enough to lead the passage of cells. Considering that one of the most studied effects of PDT consists of the vascular damage which is achieved by controlling the time interval between PS intravascular injection and illumination, the photoinduced damage of ECs could cause massive destruction that produce vessel collapse and thrombus formation (Karwicka et al., 2019; Lepor, 2008). However, in targeted vascular PDT and with the aim of generating leakage from capillaries, appropriate irradiation dosage must be managed to increase vessel permeability but not induce occlusion; because in this last scenario the arrival of drugs and cells to tumor may be interrupted.…”
Section: The Opening Of Bbb By Pdtmentioning
confidence: 99%
“…ФДТ -метод лечения онкологических заболеваний, а также некоторых заболеваний кожи (псориаз, ихтиоз, гнойничковые заболевания и др.) или инфекционных заболеваний, воспалительных заболеваний слизистых (в т. ч. хронического пародонтита), основанный на применении фотосенсибилизаторов и лазерного излучения определённой длины волны [10][11][12][13][14][15][16].…”
Section: Introductionunclassified
“…There are three main mechanisms of PDT: the direct killing of cancer cells by photogenerated reactive oxygen species (ROS), tumor-associated vascular damage and activation of anti-tumor immune responses [2,4]. These mechanisms suggest that intricate relations between the nature of the photosensitizer (PS), PS dose, light dose, drug-to-light interval (DLI), the oxygen concentration in the targeted tissue and the mechanism of cell death [2,[5][6][7] are likely to affect the outcome of PDT efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, longer drug-to-light intervals (DLI > 12h) are used [8][9][10][11]. At intermediate DLIs (e.g., 3 h) the PS is found mainly in the blood and endothelial cells, with partial accumulation in tumor cells [6,12], and protocols using such intermediate DLIs are designated here as E-PDT.The first step in PDT is the selection of a PS with physicochemical and pharmacological properties adequate for the intended PDT regime [13]. The hydrophilicity/lipophilicity of the PS is one of the most important factors influencing its biological behavior, including uptake by cancer cells, intracellular localization, biodistribution and pharmacokinetics [14,15].…”
mentioning
confidence: 99%
See 1 more Smart Citation